Predicting in vivo cardiovascular properties of β-blockers from cellular assays: a quantative comparison of cellular and cardiovascular pharmacological responses - Baker, Jillian G.; Kemp, Philip; March, Julie; Fretwell, Laurice; Hill, Stephen J.; Gardiner, Sheila M. (Federation of American Society of Experimental Biology, 2011)
β-Adrenoceptor antagonists differ in their degree of partial agonism. In vitro assays have provided information on ligand affinity, selectivity, and intrinsic efficacy. However, the extent to which these properties are manifest in vivo is less clear. Conscious freely moving rats, instrumented for measurement of heart rate (β1; HR) and hindquarters vascular conductance (β2; HVC) were used to measure receptor selectivity and ligand efficacy in vivo. CGP 20712A caused a dose-dependent decrease in basal HR (P<0.05, ANOVA) at 5 doses between 6.7 and 670 μg/kg (i.v.) and shifted the dose-response curve for isoprenaline to higher agonist concentrations without altering HVC responses. In contrast, at doses of 67 μg/kg (i.v.) and above, ICI 118551 substantially reduced the HVC response to isoprenaline without affecting HR responses. ZD 7114, xamoterol, and bucindolol significantly increased basal HR (ΔHR: +122±12, +129±11, and +59±11 beats/min, respectively; n=6), whereas other β-blockers caused significant reductions (all at 2 mg/kg i.v.). The agonist effects of xamoterol and ZD 7114 were equivalent to that of the highest dose of isoprenaline. Bucindolol, however, significantly antagonized the response to the highest doses isoprenaline. An excellent correlation was obtained between in vivo and in vitro measures of β1-adrenoceptor efficacy (R2=0.93; P<0.0001).—Baker, J. G., Kemp, P., March, J., Fretwell, L., Hill, S. J., Gardiner, S. M. Predicting in vivo cardiovascular properties of β-blockers from cellular assays: a quantitative comparison of cellular and cardiovascular pharmacological responses.